Motor control patterns during an active straight leg raise in pain-free subjects - Beales, Darren; O apos Sullivan, P.; Briffa, Kathy (Lippincott, Williams and Wilkins, 2009)
STUDY DESIGN.: Repeated measures. OBJECTIVE.: To investigate motor control (MC) patterns of normal subjects during the low level physical load of the active straight leg raise (ASLR). SUMMARY OF BACKGROUND DATA.: Aberrant MC patterns, as observed with the ASLR test, are considered to be a mechanism for ongoing pain and disability in subjects with chronic musculoskeletal pelvic girdle pain. These patterns may not only affect the provision of lumbopelvic stability, but also respiration and the control of continence. Greater understanding of MC patterns in pain-free subjects may improve the management of pelvic girdle pain. METHODS.: Fourteen pain-free nulliparous women were examined during the ASLR. Electromyography of the anterior abdominal wall, right chest wall and the anterior scaleni, intraabdominal pressure (IAP), intrathoracic pressure (ITP), respiratory rate, pelvic floor kinematics, and downward leg pressure of the nonlifted leg were compared between a left and right ASLR. RESULTS.: There was greater activation of obliquus internus abdominis and obliquus externus abdominis on the side of the ASLR. The predominant pattern of activation for the chest wall was tonic activation during an ipsilateral ASLR, and phasic respiratory activation lifting the contralateral leg. Respiratory fluctuation of both IAP and ITP did not differ lifting either leg. The baseline shifts of these pressure variables in response to the physical demand of lifting the leg was also the same either side. There was no difference in respiratory rate, pelvic floor kinematics, or downward leg pressure. CONCLUSION.: Pain-free subjects demonstrate a predominant pattern of greater ipsilateral tonic activation of the abdominal wall and chest wall on the side of the ASLR. This was achieved with minimal apparent disruption to IAP and ITP. The findings of this study demonstrate the plastic nature of the abdominal cylinder and the flexibility of the neuromuscular system in controlling load transference during an ASLR. © 2008, Lippincott Williams & Wilkins.